Слава столетия: ист. повести / В. Б. Муравьев ; худ. Л. Фалин - Муравьев Владимир Брониславович (Детская литература, 1979)
Экземпляры: (20170321) / Инвентарный номер: 11057 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М 91 / ББК: 84(2Рос=Рус)6